2012
DOI: 10.1029/2011jd016377
|View full text |Cite
|
Sign up to set email alerts
|

Large‐amplitude gravity waves above the southern Andes, the Drake Passage, and the Antarctic Peninsula

Abstract: Above the southern Andes range and its prolongation in the Antarctic Peninsula, large‐amplitude mountain and shear gravity waves observed with Weather Research and Forecasting (WRF) mesoscale model simulations during winter 2009 are analyzed. Two specific reasons motivated this study: (1) a decade of satellite observations of temperature fluctuations in the stratosphere, allowing us to infer that this region may be launching the largest‐amplitude gravity waves into the upper atmosphere, and (2) the recent desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
4
32
0
Order By: Relevance
“…Many observational studies demonstrated that the Antarctic Peninsula is indeed a hotspot of stratospheric gravity wave activity (Wu and Jiang, 2002;Jiang et al, 2006;Baumgaertner and McDonald, 2007;Vincent et al, 2007;Hertzog et al, 2008; S. P. Hoffmann et al, 2013). Orographic waves over the Antarctic Peninsula have also been extensively studied by means of mesoscale model simulations (Plougonven et al, 2008;de la Torre et al, 2012;Noel and Pitts, 2012;Orr et al, 2014). Mountain waves generated by the peninsula are of interest not only because of their impact on atmospheric dynamics, but also because they can trigger the formation of polar stratospheric clouds.…”
Section: Case Study Of Mountain Waves Near the Antarctic Peninsulamentioning
confidence: 99%
“…Many observational studies demonstrated that the Antarctic Peninsula is indeed a hotspot of stratospheric gravity wave activity (Wu and Jiang, 2002;Jiang et al, 2006;Baumgaertner and McDonald, 2007;Vincent et al, 2007;Hertzog et al, 2008; S. P. Hoffmann et al, 2013). Orographic waves over the Antarctic Peninsula have also been extensively studied by means of mesoscale model simulations (Plougonven et al, 2008;de la Torre et al, 2012;Noel and Pitts, 2012;Orr et al, 2014). Mountain waves generated by the peninsula are of interest not only because of their impact on atmospheric dynamics, but also because they can trigger the formation of polar stratospheric clouds.…”
Section: Case Study Of Mountain Waves Near the Antarctic Peninsulamentioning
confidence: 99%
“…Regarding the possible penetration of tropospheric waves, not necessarily larger amplitude waves are expected to produce larger effects at ionospheric heights. From mesoscale modeling results, single events of large amplitude MWs near the Andes are found to enhance wave activity to the eastern side and to transfer momentum flux to the background atmosphere at relatively low stratospheric heights [de la Torre et al, 2012]. Small/moderate amplitude GWs could be more likely to reach saturation and breaking levels at higher altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…In the southern Hemisphere, there are extratropical regions that exhibit strong wave activity close to the Andes and to the Antarctic Peninsula (e.g., Eckermann and Preusse, 1999;de la Torre et al, 2012;Hierro et al, 2013 -hereinafter, HI13-). A considerable number of deep valleys mainly aligned from north to south are a scenario for the development of strong and frequent convection events between late spring and early autumn, sometimes followed by the production of hailstorms causing severe damage.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Internal gravity waves (GWs) and in particular mountain waves (MWs) are one of the most important energy and momentum transport mechanisms throughout the atmosphere (e.g. de la Torre et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%